Circ0083429 Regulates Osteoarthritis Progression via the Mir-346/SMAD3 Axis - Yao, Teng; Yang, Yute; Xie, Ziang; Xu, Yining; Huang, Yizhen; Gao, Jun; Shen, Shuying; Ye, Huali; Iranmanesh, Yasaman; Fan, Shunwu; Ma, Jianjun (Frontiers in Cell and Developmental Biology, 2021)
Osteoarthritis (OA) is a degenerative joint disease. Currently, apart from symptomatic treatment or joint replacement, no other effective treatments for OA exist. The mechanisms underlying OA remain elusive and require further research. Circular RNAs are known to be involved in many diseases; however, their function in OA is not yet fully understood. Here, we identified a novel circular RNA (CircRNA), Circ0083429. The role of Circ0083429 in OA was confirmed via western blotting (WB), quantitative real-time PCR (qRT-PCR), and immunofluorescence (IF) through knockdown and overexpression experiments. The binding of Circ0083429 to downstream miR-346 and its target gene SMAD3 was predicted via bioinformatics analysis and verified using luciferase reporter assay and RNA pulldown experiments. Finally, the function of Circ0083429 was evaluated in mouse OA models. In our study, we found that Circ0083429 regulates the homeostasis of the extracellular matrix (ECM) in human chondrocytes. Mechanistically, Circ0083429 affects OA by regulating the mRNA level of SMAD3 through the sponging of miRNA-346. Injecting adeno-associated virus-Circ0083429 into the intra-junction of the mouse knee alleviated OA. In conclusion, Circ0083429 regulates the ECM via the regulation of the downstream miRNA-346/SMAD3 in human chondrocytes, which provides a new therapeutic strategy for OA.